Research on Migration or Deployment of Telecom Network Management System on Cloud Computing Network - Afang Song; Lian Lin; Faguang Wang (Dianxin kexue)
According to the present situation of cloud computing technology and communication network management system，the existing network management system on the server hardware type，storage mode，special peripherals，and disaster recovery aspects of clouding related features were analyzed. Some key problems of system migration or deployment process on cloud computing network were analyzed. The specific method of system resources distribution and calculation，expansion reference coefficients，Oracle database cloud concern points，double disaster recovery system，same city or remote cities disaster recovery systems in cloud solutions were explored. A cloud migration scheme of fully meet or part to meet network management systems was proposed.